2019
DOI: 10.3390/w11122497
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship between Suspended Sediment Concentration, Rainfall Variability and Groundwater: An Empirical and Probabilistic Analysis for the Andean Beni River, Bolivia (2003–2016)

Abstract: Fluvial sediment dynamics plays a key role in the Amazonian environment, with most of the sediments originating in the Andes. The Madeira River, the second largest tributary of the Amazon River, contributes up to 50% of its sediment discharge to the Atlantic Ocean, most of it provided by the Andean part of the Madeira basin, in particular the Beni River. In this study, we assessed the rainfall (R)-surface suspended sediment concentration (SSSC) and discharge (Q)-SSSC relationship at the Rurrenabaque station (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The reported changes in the inter-annual variability of rainfall during the DJF wet season suggest possible changes at shorter time scales (i.e., daily or hourly), probably affecting rainfall erosivity. Ayes et al (2019b) found a long-term coincidental peak of rainfall and SSSC at Rurrenabaque in January. As expected from the high correlation between monthly rainfall and SSSC, the same authors identified a linear function relating the direct surface flow and SSSC at Rurrenabaque for the 2003-2016 period.…”
Section: Causes Of the Decreasing Trend Of Sssc At Porto Velho Stationmentioning
confidence: 87%
See 3 more Smart Citations
“…The reported changes in the inter-annual variability of rainfall during the DJF wet season suggest possible changes at shorter time scales (i.e., daily or hourly), probably affecting rainfall erosivity. Ayes et al (2019b) found a long-term coincidental peak of rainfall and SSSC at Rurrenabaque in January. As expected from the high correlation between monthly rainfall and SSSC, the same authors identified a linear function relating the direct surface flow and SSSC at Rurrenabaque for the 2003-2016 period.…”
Section: Causes Of the Decreasing Trend Of Sssc At Porto Velho Stationmentioning
confidence: 87%
“…The negative SSSC trend in February detected at Porto Velho deserves a more comprehensive explanation. Whereas, the sediment recorded at Porto Velho in February comes from the Andes, the sediment dynamics at this time of the year is already influenced by the dilution associated with the base flow at Rurrenabaque (Ayes et al, 2019b). At Porto Velho, the already significant sub-surface and base flow coming from different parts of the floodplain (Miguez-Macho and Fan, 2012;Frappart et al, 2019) also contributes to dilution.…”
Section: Causes Of the Decreasing Trend Of Sssc At Porto Velho Stationmentioning
confidence: 97%
See 2 more Smart Citations
“…However, hysteresis has been known for a long time in soil physics and soil hydrology and associated with water flowing through porous media [68,92]. Furthermore, hysteresis is found in surface hydrology, where sediment transport studies in streams show that sediment yields may depict such behaviour, as well as ionic species dissolved or adsorbed to the soiled phase [64,93,94].…”
Section: Soil Water Recharge and Depletionmentioning
confidence: 99%